Students’ Perceptions of using Machine Translation Tools in the EFL Classroom - Geno Bagas Prayoga (Universitas Muhammadiyah Prof. DR. HAMKA, 2022)
Machine translation is a technology that can automate the process of translating text or speech from one language to another, and has become a leading technology in the current era of information technology. This study explores students’ perception about the use of machine translation in English learning activities. The purpose of this study is specifically to find out whether and how machine translation is seen as an effective substitute for conventional dictionaries, and can help and facilitate students in learning English. The population of this study were higher education students in one private University in Jakarta. This study used online closed-ended questionnaire as the main instrument. The respondents of this study were 106 students in Jakarta. The data was then analysed on the corridor of the quantitative approach with survey design. The results of this study showed that machine translation was very good in terms of features and displays (60.38%), very easy to use (83.96%), provide motivation to learn English (62.26%), satisfaction to use (50.00%) and English competence (82.18%). from the results of the data it can be seen that machine translation is very easy to use, very helpful, very interesting, and can provide interest in learning English. Keyword: EFL, English Learning, Machine Translation, Perception.